COMPARATIVE INVESTMENT ANALYSIS OF RECOMMENDED COCONUT HYBRIDS/CULTIVARS FOR THE NATIONAL PLANTING/REPLANTING PRO¬GRAM IN THE PHILIPPINES - G. A. Santos; S. M. Rivera; R. L. Rivera; G. B. Baylon; B.V. dela Cruz (International Coconut Community, 1995)
Comparative investment analysis was done on the eight coconut hybridsl cultivars under the Zamboanga condition using the Multiple Budget (MULBUD) program. The, study aims to ovaluate and compare the economic profitability qf coconut hybrids/cultivars under two planting schemes and determine the best genetic materials that will provide the highest economic returns to coconut farmers. Analysis of the recommended varieties was also done using different product groups and coco‑based enterprises. The economic performance of each coconut hybrids1cultivars was measured using investment indicators like SNPV, BCR, and IRR. With copra and shell as products under the new planting scheme, the use of PCA recommended local hybrids and BAY is a more profitable investment compared with MAWA and the other tall populations. In general, the profit‑ability of coconut hybrids and cultivars was enhanced under the replanting scheme. Break even point was attained at year one due to the value of coconut timber obtained from the old stand. Results further indicated that the use of local hybrids and BAY is the best starting point in increasing farm income. However, higher returns were obtained when product utilization are diversified and coco‑based enter‑ prises are incorporated.